Outcomes Of Vision Therapy Among Children with Cerebral Visual Impairment: A Retrospective Study. - Chakraborty, Shoubhik; Sarbajna, Puja; Vinekar, Anand; Shetty, Bhujang (Optometry & Visual Performance, 2024)
Background: Cerebral visual impairment (CVI) is a complex neurodevelopmental disorder and a major cause of low vision in both developed and developing countries. Over the past two decades, atypical causes, such as treatable or preventable conditions like cataracts and retinopathy of prematurity (ROP), have emerged. Vision plays a crucial role in guiding our limbic system to achieve its goals, and any delay in visual development can lead to delays in overall developmental milestones. Methods: Demographic information, as well as essential prenatal, perinatal, and postnatal histories, were recorded for all 27 patients. The subjects were divided into three groups: clinically confirmed CVI based on characteristics of CVI (n=9), hypoxic-ischemic encephalopathy (n=9); and hypoglycemia (n=9). Visual acuity evaluation was conducted using the Teller Acuity Cards and Lea Paddles in a cycles-per-degree format. Due to monocular occlusion resistance, vision was recorded binocularly, as binocular vision is sufficient for functional aspects. Cycloplegic refraction was performed for all children. The Hirschberg test was employed to rule out apparent ocular deviation, while the ophthalmologist examined the anterior segment with a torch or handheld slit lamp and assessed the fundus with an indirect ophthalmoscope. Results: The study observed visual improvement post-vision therapy based on visual acuity, with an overall success rate of 81.48% (22 out of 27). The visual prognosis for different groups was 100% (9 out of 9), 66.67% (6 out of 9), and 77.78% (7 out of 9), respectively. Conclusions: The increased survival rate of preterm and neuro-compromised babies has led to a rise in the prevalence of complex visual impairments like CVI. Although these pathologies may not be visible through MRI, the presence of the CVI marker on OCT confirmed the diagnosis, correlating with classical features of CVI, such as movement preference, light gazing, and variable menace. Additionally, the absence of pathologies in the MRI scan indicated good visual recovery following vision therapy.